The Development of Mobile Augmented Reality-Based Science Learning Media on Earth Layer Materials and Disasters in Class VII Junior High School - Miftahul Farhani Isty; M. Nor; Muhammad Sahal (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2021)
This research aims to produce products in the form of printed modules and CDs containing augmented reality (AR) applications. The AR application on the CD was transferred to the mobile phone and installed. Augmented reality technology in the form of 3D animation and video appears by scanning markers or images in the module using the AR application camera on the mobile phone. One of the 3D animations shown is an animation of the earth, while one of the videos shown is a video about layers in the Earth's atmosphere. This research method uses research and development R&D (Research and Development) with the ADDIE model development model. The ADDIE model consists of analysis, design, development, implementation, and evaluation. This research is only up to the development stage. The source of the data used in this research is the assessment score that comes from a questionnaire in the form of a checklist filled out by an expert validator. The data obtained showed that the material validation score was 3.48 (high category) and the media validation score was 3.51 (very high category). The results of this research indicate that the mobile augmented reality-based science learning media on the Earth layer and disaster material has been valid in terms of material and media, so it is suitable to be used as a learning media for the Earth layer and disaster in class VII junior high school.